Florfenicol concentrations in milk of lactating cows postreated by intramuscular or intramammary routes (2010)
ABSTRACT: Objective. To determine the florfenicol concentration in bovine milk after intramuscular or intramammary administration to establish the optimum withdrawal time, therapeutic efficacy, and its influence on milk yield. Materials and method. Twelve healthy lactating Holstein cows were selected from the University of Antioquia’s teaching dairy herd (Colombia), were randomly assigned to a control (n=6) group or florfenicol (n=6) group that received 20 mg/kg of florfenicol by intramammary and intramuscular routes, with a 15 days washout period between treatments. Results. The Tmax and Cmax for the intramuscular route were 6 hours and 2.86 mg/L respectively. The Tmax and Cmax for the intramammary route, were estimated at 0 hour and about 20000 mg/L respectively by extrapolated from regression line. The florfenicol elimination phase in milk had an average half-life of elimination (t½) of 19.8 hours and 4.9 hours for intramuscular and intramammary administration, respectively. The therapeutic efficacy only was reached by intramammary route, when minimal inhibitory concentration (M.I.C.) of florfenicol by Stahphylococcus aureus, was used as reference value. There was no statistically significant difference in milk yield between treated and non-treated cows. Conclusions. According to these results, post-treatment milk withdrawal should be no less than 3 days for intramammary administration, and at least 7 days for intramuscular administration. The therapeutic efficacy only was reached by intramammary route. In addition, there was no statistically significant difference in milk yield between treated and nontreated cows.